Impact of chronic osteomyelitis on wound healing and the quality of life of the patient with a chronic wound - Swapna Johnson-Kunjukutty and & Carmel Delille (WCET Journal - Chinese Edition, 2019)
Spinal cord injury (SCI) patients have a higher risk of developing pressure injury secondary to limited mobility and lack of sensation. The James J Peters Medical Center is one of several regional spinal cord injury centres in the Veterans Affairs System. Veterans with SCI receive comprehensive care. Hospital- and community-acquired pressure injuries (HAPIs and CAPIs) can progressively advance to chronic stage IV pressure injury complicated with osteomyelitis. Chronic wounds that become infected can lead to sepsis if the wounds are not managed properly. The management of chronic wounds represents a significant financial burden for any health care system and a challenge for providers whose goals are to avoid prolongation of hospital stay, avoid complications, and minimise disruption in the patient’s life. A focus of the primary physician is to establish a rehabilitation plan that facilitates the patient to resume activities of daily living post injury and have a productive life in their community. However, despite the collaborative effort of the SCI team, the sudden change in the patient’s mobility can also have a detrimental impact on the patient’s mental status as well.